Synthesis and antitumor mechanism of a new iron(iii) complex with 5, 7-dichloro-2-methyl-8-quinolinol as ligands12. Issue 3 (14th February 2017) - Zou, Bi-Qun; Qin, Qi-Pin; Bai, Yu-Xia; Cao, Qian-Qian; Zhang, Ye; Liu, Yan-Cheng; Chen, Zhen-Feng; Liang, Hong
Abstract : A new iron(iii ) complex with 5, 7-dichloro-2-methyl-8-quinolinol (HClMQ) as ligands, i.e., [Fe(ClMQ)2 Cl] (1 ), was synthesized and evaluated for its anticancer activity. Abstract : A new iron(iii ) complex with 5, 7-dichloro-2-methyl-8-quinolinol (HClMQ) as ligands, i.e., [Fe(ClMQ)2 Cl] (1 ), was synthesized and evaluated for its anticancer activity. Compared to the HClMQ ligand, complex1 showed a higher cytotoxicity towards a series of tumor cell lines, including Hep-G2, BEL-7404, NCI-H460, A549, and T-24, with IC50 values in the range of 5.04–14.35 μM. Notably, the Hep-G2 cell line was the most sensitive to complex1 . Mechanistic studies indicated that complex1 is a telomerase inhibitor targeting c-myc G-quadruplex DNA and can trigger cell apoptosis via inducing cell cycle arrest and DNA damage.